The BRICS and Africa's search for green growth, clean energy and sustainable development. (September 2018) - Gu, Jing; Renwick, Neil; Xue, Lan
Abstract: The BRICS group of countries is widely held to offer the prospect of a new approach to sustainable development, renewable energy and green economic growth in Africa. This paper examines the BRICS' approach to renewable energy cooperation. It argues that, following a robust declaratory intent, implementation has taken time to achieve but there are signs of this coming on-stream. The New Development Bank can provide an effective intervention mechanism for the BRICS in Africa. New BRICS' policy initiatives suggest a more accelerated approach on renewable energy investment and technological cooperation. However, for the foreseeable future, individual members will be the drivers of the transfer process, particularly China and India. In terms of policy, the BRICS need to elaborate a specific strategy for renewable energy cooperation for both intra-BRICS and extra-BRICS development. Policies should also prioritise their pro-poor rationale and intent to widen energy access, achieve energy equity and overcome energy poverty. China and India have a significant existing and growing capacity to help move this forward. Highlights: BRICS is important for Africa's promotion of renewable energies (RE) and green growth. BRICS provides for collective engagement, but individual members are the main drivers. BRICS-Africa policies on RE and green growth must be synchronised via pro-poor aims.